Identification of disulfiram as a potential antifungal drug by screening small molecular libraries. Issue 5 (May 2021) - Hao, Weifeng; Qiao, Dan; Han, Ying; Du, Ning; Li, Xuefen; Fan, Yufeng; Ge, Xuejun; Zhang, Heyu
Abstract: Objectives: Candida albicans and Candida auris strains are common causative species of Candidiasis. The limited number of antifungal drugs and the current situation of resistance to existing antifungals force us to search for new antifungal alternatives. Methods: In this work, primary screening of small molecule libraries (Metabolism Compound Library and Epigenetics Compound Library) consisting of 584 compounds against Candida albicans SC5314 was performed. The dose-response assays, XTT assays, scanning electron microscopy and confocal laser scanning microscopy were used to confirm the antifungal activities of the selected compounds against Candida strains. Results: Through the primary screening, we identified five compounds (U73122, disulfiram, BSK805, BIX01294, and GSKJ4) that inhibited strains growth ≥ 80% for dose-response assays. Disulfiram was identified as the most potent repositionable antifungal drug with 50% growth inhibition detected at a concentration as low as 1 mg/L. The further results showed the antifungal activity of disulfiram against biofilm formation of Candida strains with a 50% minimum inhibitory concentration ranging from 32 to 128 mg/L. Further observations by scanning electron microscopy and confocal laser scanning microscopy confirmed the destruction of biofilm architecture and the change of biofilm morphology after being exposed to disulfiram. Conclusion: The study indicated the potential clinical application of disulfiram as a promising antifungal drug against candidiasis.